Telmisartan/hydrochlorothiazide single-pill combination in the treatment of hypertension in elderly patients. (April 2011) - Neldam, Steen; Guthrie, Robert M
Telmisartan is an angiotensin II receptor blocker that differs from others in its class owing to its unique pharmacologic properties, such as high lipophilicity and a long elimination half-life. It is the only angiotensin II receptor blocker indicated for the prevention of cardiovascular morbidity (such as myocardial infarction or stroke in patients with atherothrombotic disease or diabetes with end-organ damage), as well as hypertension. It provides sustained 24-h blood pressure control with once-daily dosing. Combination with hydrochlorothiazide provides additional antihypertensive effect in patients who are unable to achieve target blood pressure with either monotherapy. A single-pill combination simplifies dosing, is well tolerated, encourages adherence and is proportionally cheaper, thus providing an effective therapeutic option for the treatment of elderly hypertensive patients.